Evaluation of WLAN Network Speed Based on Service Access Time and Proposed Expansion of Guest Network Infrastructure at BPJS Ketenagakerjaan Palembang Branch - Muhamad Faqih Febriansyah; Ahmad Haidar Mirza (CV. ALIM'SPUBLISHING, 2026)
This study evaluates the performance of the existing WLAN network on the first floor of the BPJS Ketenagakerjaan Palembang Branch office and proposes an expansion of guest network infrastructure on the second floor. Network performance was measured using Wireshark and Speedtest across three access-time scenarios (busy, moderate, and quiet hours), based on the TIPHON Quality of Service parameters: throughput, delay, jitter, and packet loss. Results show that the existing flat-network topology causes severe performance degradation during busy hours, with a QoS index of 2.00 (fair/critical), throughput dropping to 0.96 Mbps, delay rising to 338 ms, jitter spiking to 792.6 ms, and packet loss reaching 9.35%. Based on these findings, a second-floor guest network design is proposed using VLAN segmentation, a captive portal with a two-hour session limit, and per-user bandwidth throttling of 2 Mbps. The proposed design isolates public traffic from the internal network while maintaining fairness of access for visitors, offering a practical and secure solution for expanding wireless infrastructure in public-service institutions.